OPTIMALISASI PEMBELAJARAN MELALUI PENGABDIAN MAHASISWA PAI DI SMK ISLAM 45 WIRADESA - Khozin, Muhammad; Dewi, Susiana; Nurfalasyifa, Mutia; Magfiroh, Luluk Agustin Maryatul; Lathifah, Meyta; Rohman, Ahmad Luthfi Hidayatur; Dany, Muhammad Amhar; Darais, Rena Anzahra; Prasetya, Sulistiana; Anjalina, Ghina Karima (Mafaza : Jurnal Pengabdian Masyarakat, 2024)
The Community Service Program (PkM) through Field Experience Practices (PPL) run by Islamic Religious Education students of the Faculty of Tarbiyah and Teacher Training at K.H. Abdurrahman Wahid Islamic University Pekalongan aims to strengthen teaching skills and understanding of the world of education for prospective teachers. The program is implemented at SMK Islam 45 Wiradesa and utilizes the Lesson Study method as a sustainable coaching approach that emphasizes collaboration between students, teachers, and supervisors. Lesson Study is implemented in three stages: Design (Plan), Implementation (Do), and Evaluation (See), in order to improve the quality of learning and facilitate a deeper understanding of teaching and learning dynamics. The implementation of PPL showed positive results, with active involvement between students and teaching staff in the preparation of materials, teaching practice, and evaluation. As a result of this activity, students can improve their skills in designing lessons, managing classes, and developing good relationships with students. However, challenges are also faced in terms of time management, managing student behavior, and limited resources. With continuous evaluation, this program proved to be beneficial not only for students but also for improving the quality of education in partner schools.